Sustainable Pesantren: Institutional Reform In Islamic Education - Mainuddin; Ishomuddin; Faridi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This study examines the approach of institutional transformation in Islamic education inside pesantren, with the aim of establishing a sustainable educational institution. The work is guided by a single problem formulation: How may pesantren attain sustainability through institutional change in Islamic education? This study employs a qualitative research methodology with a literature review framework. This study employs a content analysis methodology for its analysis. The dataset utilised in this investigation comprises scholarly journal articles and conference proceedings. The acquisition of all literary works is accomplished by conducting a search on Google Scholar using specific keywords: “Pembaharuan, Pesantren, Pendidikan Islam”. This study demonstrates the long-term viability of institutional transformation in Islamic education within pesantren through many approaches: 11) Diversification in pesantren leadership; 2) Diversification of educational institutions; 3) Integration of the Classical education curriculum with religious education with science; 4) Technology-based education; 5) Responsive to the times; and 6) Restructuring of educational institutions. This study enhances comprehension of the methodology employed by pesantren in rejuvenation, ensuring their continued relevance to contemporary demands while upholding their historic principles.